London, Queer Spaces and Historiography in the Works of Sarah Waters and Alan Hollinghurst - Neves, Júlia Braga (Queer studies., 2022)
Queer spaces are crucial for the construction of LGBTQ+ communities, as they constitute places where queer subjects can create political, social, and affective alliances. Júlia Braga Neves shows how these spaces are pivotal for the representation of queer history in the fictional works by the British authors Sarah Waters and Alan Hollinghurst, whose characters and plots are articulated through and within London's sexual geographies. Considering the intersection between gender, sexuality, and class, this study engages with spatial, queer, feminist, and Marxist theories as a means to reflect on London, queer historiography, and the relationship between subject and urban space.